2014
DOI: 10.1002/phar.1414
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Clinical Pharmacy Services: 2006–2010

Abstract: Studies have consistently evidenced the positive clinical, economic, and humanistic benefits of pharmacist-directed patient care in a variety of settings. Given the vast differences in clinical outcomes associated with evaluated clinical pharmacy services (CPS), more detail as to the nature of the CPS is needed to better understand observed differences in economic outcomes. With the growing trend of outpatient pharmacy services, these economic evaluations serve as viable decision-making tools in choosing the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 41 publications
4
122
1
Order By: Relevance
“…Previous review articles have broadly reached the same conclusion, the operation of additional clinical pharmacy services results in cost savings to the healthcare payer [10][11][12][13][14]. However, many published studies have been of poor quality [12,14], limiting the strength of any conclusions presented in previous reviews.…”
Section: Introductionmentioning
confidence: 89%
“…Previous review articles have broadly reached the same conclusion, the operation of additional clinical pharmacy services results in cost savings to the healthcare payer [10][11][12][13][14]. However, many published studies have been of poor quality [12,14], limiting the strength of any conclusions presented in previous reviews.…”
Section: Introductionmentioning
confidence: 89%
“…The physicians' fear of losing independence and professional autonomy is one of the barriers and reasons for the negative attitude towards clinical pharmacists, perceived as inspectors of their work (5,6). On the other side, there is a growing number of literature data about the positive economic impact of clinical pharmacists´ activities (7).…”
Section: Abstract: Clinical Pharmacist Activities Physicians Nursesmentioning
confidence: 99%
“…43 In another systemic review from three studies between 2006 and 2010, Touchette et al reported benefit versus cost ratio ranges from 1.05:1 to 25.95:1, a hospital saving ranges as little as $1.05 to $25.95 for every $1 invested in clinical pharmacy. 44 The broad range of the benefit versus cost ratio can be due to a number of clinical pharmacists required per institution, the pharmacist hiring salary, and pharmacist time spent on interventions might vary in each institution.…”
mentioning
confidence: 99%